Filozoficzne przesłanki pojmowania systemowości prawa w teorii wykładni Jerzego Wróblewskiego - Pulka, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
That is to say that Jerzy Wróblewski’s theory of interpretation assumes philosophical attitude consisting in acceptance of Marxist philosophy. Consequently, Jerzy Wróblewski’s theory of interpretation may be counted as theory of interpretation of “people’s law”. The author tends to point out that the notion of “people’s law” is a philosophical category, i. e. the main traits of “peoples law” are defined on the level of Marxist philosophy. Consequently, all propositions of Jerzy Wróblewski’s theory of interpretation are propositions which presuppose existence of such conceived “people’s law”. In the article, the author strives to point out that philosophical assumptions of Marxist philosophy determine Jerzy Wróblewski’s way of conceiving the systemic character of law.
Keywords: teoria prawa; Wróblewski, Jerzy (1926-1990); filozofia prawa